Imobilização de lipases pela técnica CLEA para síntese de biodiesel em reator de fluxo em vórtice - Díaz-Ramos, Margarita (Universidade Federal de São Carlos, 2017)
Due to the heterogeneity of the vegetable oils used in the synthesis of biodiesel, they can be transformed more quickly using a mixture consisting of lipases with different activities and specificities instead of single lipases. In this context, this PhD work aimed to evaluate the enzymatic synthesis of biodiesel in vortex flow reactor catalyzed with a mixture of lipases. The lipases were selected and later immobilized by a low-cost technique known as CLEA (cross-linked enzyme aggregate). Mixtures of two lipases from different sources including Thermomyces lanuginosus (TLL), Candida antarctica fraction B (CALB), porcine pancreas (PPL) and Pseudomonas fluorescens (PFL) lipases were evaluated in the transesterification of soybean oil. The mixture of 50 % of PPL and 50 % of TLL reached the highest concentration of fatty acid ethyl esters (FAEE). Under the conditions evaluated, it was obtained 22.03% in 8 h, whereas the individual lipases, TLL and PPL reached 4.32 % and 0.22 % of FAEE, respectively. These lipases were individually immobilized by CLEA technique and evaluated (individually and mixed) in the ethylic transesterification of soybean oil. The PPL CLEA, called PPL-SP-CLEA, reached around 60 % FAEE, a concentration 12 times higher than that achieved with soluble PPL after 34 h of reaction and with a 2-fold lower enzymatic loading. On the other hand, the LTL CLEA, called LTL-SDS-CLEA, was prepared using ethanol as a precipitant, the surfactant sodium dodecyl sulfate (SDS) and glutaraldehyde. The CLEAs LPP-PS-CLEA and LTL-SDS-CLEA were used in a mixture (50 % - 50 %) to catalyze the transesterification of soybean oil. The use of the mixture within 48 hours of reaction resulted in the increase of the final FAEE concentration of almost 20% relative to the individual CLEAs. Through 10 h of reaction, the mixture of CLEAs reached 90% of the FAEE mass concentration. Finally, this mixture was evaluated in the vortex flow reactor, reaching 86.1% of FAEE in 6 h of reaction and saving nearly 80% of activity through 5 cycles of reaction. The mixture of CLEAs LPP-PS-CLEA and LTL-SDS-CLEA showed to be a potential approach to improve the rate of the transesterification reaction, by the synergistic action of lipases.
Immobilization of lipases by CLEA technique for synthesis of biodiesel in vortex flow reactor
Keywords: Biodiesel; Lipase; Transesterificação; Imobilização; Reator de fluxo em vórtice; Cross-linked enzyme aggregates CLEA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA